2015
DOI: 10.1039/c4ra17268j
|View full text |Cite
|
Sign up to set email alerts
|

Properties modification by eutectic formation in mixtures of ionic liquids

Abstract: The composition and temperature of three eutectic mixtures of ionic liquids and their physical properties (density, viscosity, and surface tension) are presented. Melting temperature depressions of up to ca. 50 K were found with regard to those of the parent ionic liquids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…All DSC runs were performed two times independently. The melting points of the pure ionic liquids are shown in Table , and acceptable agreement in the transition temperatures with published data has been observed for the pure compounds ([C 4 C 1 Im]­[NO 3 ], [C 4 C 1 Im]­[CH 3 SO 3 ], and [C 4 C 1 Im]­Cl). This table also presents the glass-transition and solid-phase transition temperatures determined in this work. For [C 4 C 1 Im]­[NO 3 ], a solid–solid transition at T = 279 K was also observed, which is in accordance with the values reported by Strechan et al The presence of polymorphs in the nitrate family of ILs has been already studied and confirmed by several authors. , Furthermore, the metastability of [C 4 C 1 Im]­Cl was herein noticed, with the melting temperature present in the second heating cycle at T = 342 K without further crystallization in the following cycles.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…All DSC runs were performed two times independently. The melting points of the pure ionic liquids are shown in Table , and acceptable agreement in the transition temperatures with published data has been observed for the pure compounds ([C 4 C 1 Im]­[NO 3 ], [C 4 C 1 Im]­[CH 3 SO 3 ], and [C 4 C 1 Im]­Cl). This table also presents the glass-transition and solid-phase transition temperatures determined in this work. For [C 4 C 1 Im]­[NO 3 ], a solid–solid transition at T = 279 K was also observed, which is in accordance with the values reported by Strechan et al The presence of polymorphs in the nitrate family of ILs has been already studied and confirmed by several authors. , Furthermore, the metastability of [C 4 C 1 Im]­Cl was herein noticed, with the melting temperature present in the second heating cycle at T = 342 K without further crystallization in the following cycles.…”
Section: Resultssupporting
confidence: 77%
“…All of the samples, because of their hygroscopic character, were prepared in a glovebox. Thermophysical data were collected at atmospheric pressure accordingly to the method developed by Stolarska et al 31 All of the samples were initially heated from room temperature at a rate of 2.5 K min −1 . At this temperature, they were held for an isotherm of 25 min, prior to two cycles of cooling and heating at a rate of 2.5 K min −1 spaced by 10 min isothermal holding at the lower and upper end-point temperatures.…”
Section: Journal Of Chemical and Engineering Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Since the decomposition prevents, or at least strongly hinders, the use of direct techniques for the measurement of choline chloride melting enthalpy and temperature, a work based on an indirect approach to estimate the fusion properties of [Ch]Cl was proposed by us [44]. Based on the quasi-ideal behavior of the liquid phase of mixtures of ionic liquids [45,46] [44]).…”
Section: [Ch]cl Melting Propertiesmentioning
confidence: 99%
“…His findings revealed that phosphonium-based ILs showed relatively high CO 2 capacity in general and moderate cation-anion pairing. In addition, phosphonium-based ionic liquids are generally inexpensive and available commercially on a large scale [16]. The response surface methodology (RSM), based on central composite design (CCD), was employed to optimize and to comprehend the interactions between the operating factors affecting CO 2 removal using aqueous MEA-[TBP][MeSO 3 ] hybrid solvents with different concentrations of [TBP][MeSO 3 ].…”
Section: Introductionmentioning
confidence: 99%